2014
DOI: 10.1016/j.jaci.2014.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Guselkumab (an IL-23–specific mAb) demonstrates clinical and molecular response in patients with moderate-to-severe psoriasis

Abstract: IL-23 inhibition with a single dose of guselkumab results in clinical responses in patients with moderate-to-severe psoriasis, suggesting that neutralization of IL-23 alone is a promising therapy for psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
243
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(257 citation statements)
references
References 27 publications
6
243
1
7
Order By: Relevance
“…We identified 4 independent gene expression datasets from clinical trials in psoriasis using anti-TNF (etanercept; 2 independent datasets), anti-IL-23 (guselkumab), or anti-IL-17R (brodalumab) (48)(49)(50)(51). Consistent with the gene expression results in Figure 3, in these clinical trials, GRHL3 was significantly upregulated in lesional versus nonlesional skin, and after treatment, this high level was significantly reduced to levels similar to the nonlesional controls in all but 1 etanercept trial, which still showed the correct trend (Supplemental Figure 6, A-D).…”
Section: Grhl3 Is Dispensable For Homeostatic Adult Epidermal Barriermentioning
confidence: 99%
“…We identified 4 independent gene expression datasets from clinical trials in psoriasis using anti-TNF (etanercept; 2 independent datasets), anti-IL-23 (guselkumab), or anti-IL-17R (brodalumab) (48)(49)(50)(51). Consistent with the gene expression results in Figure 3, in these clinical trials, GRHL3 was significantly upregulated in lesional versus nonlesional skin, and after treatment, this high level was significantly reduced to levels similar to the nonlesional controls in all but 1 etanercept trial, which still showed the correct trend (Supplemental Figure 6, A-D).…”
Section: Grhl3 Is Dispensable For Homeostatic Adult Epidermal Barriermentioning
confidence: 99%
“…At present, however, biologic therapies directed against only a limited number of cytokines have proven clinically effective, including TNF, IL-17A, and IL-23 [60][61][62]. Of these, IL-17A may represent the most pivotal "hub" within the cytokine network coordinating plaque development, since TNF and IL-23 appear to positively (See figure on previous page.)…”
Section: Discussionmentioning
confidence: 99%
“…It became evident that the ustekinumab clinical eicacy was related to inhibition of the IL-23 biological efect. CTLA4-Ig T cell costimulation blockade CD80, CD86 Blocking T cell activation improve psoriasis [11] LFA-3-Ig Memory T cell depletion CD2 Memory T cells are relevant in psoriasis [10] Anti-LFA-1 T cell migration and T-cell costimulation inhibitor LFA-1 Migration of T cells to psoriasis lesion is involved in disease [12] Anti-TNF-α Neutralization of biological selectively IL-23, which also has conirmed the clinical relevance of speciically blocking the IL-23/Th17 in psoriasis [16].…”
Section: Translational Research and Clinically Relevant Pathological mentioning
confidence: 92%